The psychological mechanisms of the better-than-average effect in the moral and competence domains under self-enhancement and self-protection motives among young Japanese adults - Ding, Yi; Sugiura, Motoaki (Frontiers in Psychology, 2024)
The better-than-average effect (BTAE) refers to the phenomenon where individuals perceive themselves as better than the average person. This effect has been independently examined in terms of social perception dimension and motivation. However, no psychobehavioral traits have been found to be associated with the BTAE in the moral domain. The interactive effects of social perception dimensions and motivation on the BTAE remain unclear, and its association with a broad range of psychobehavioral traits has not been extensively validated. In this study, we assess self- and average other-evaluations across four domains, based on two social perception dimensions and two motivations, to investigate their interactive effects on the BTAE (n = 678). We measured seven sets of psychobehavioral characteristics to examine their association with the BTAE, as well as self- and other-evaluations. Results indicated that the BTAE occurred only under negative moral conditions, while the worse-than-others effect was observed under two competence conditions. Furthermore, the BTAE was associated with only a few psychobehavioral characteristics in the moral domains, compared to many in the competence domains. Notably, both self- and other-evaluations were correlated with many trust-relevant characteristics in the moral domains. These findings suggest that sociocultural dynamics may influence the BTAE differently across various domains.